2016
DOI: 10.1590/1519-6984.16714
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seasonal variations and collection methods on the mineral composition of propolis from Apis mellifera Linnaeus Beehives

Abstract: The effects of seasonal variations and the methods of collection of propolis produced by Africanized honey bees Apis mellifera Linnaeus, 1758, on the composition of constituent minerals such as magnesium (Mg), zinc (Zn), iron (Fe), sodium (Na), calcium (Ca), copper (Cu), and potassium (K) were evaluated. Propolis was harvested from 25 beehives by scraping or by means of propolis collectors (screen, "intelligent" collector propolis [ICP], lateral opening of the super [LOS], and underlay method). During the one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
0
14
1
1
Order By: Relevance
“…For nickel, the sample from Taounate (S3) had the lowest quantity (0.13 mg/kg) and the sample from Boulemane (S1) had the highest concentration (2.10 mg/kg). The amount of Zn found in our studied samples is lower than that showed in 25 Brazilian propolis samples (Souza, Zaluski, Veiga, & Orsi, 2016). Micro-elements are known beneficial for our organism; in fact, they act in synergy with enzymes in the catalysis of several chemical reactions.…”
Section: Mineral Elementscontrasting
confidence: 66%
“…For nickel, the sample from Taounate (S3) had the lowest quantity (0.13 mg/kg) and the sample from Boulemane (S1) had the highest concentration (2.10 mg/kg). The amount of Zn found in our studied samples is lower than that showed in 25 Brazilian propolis samples (Souza, Zaluski, Veiga, & Orsi, 2016). Micro-elements are known beneficial for our organism; in fact, they act in synergy with enzymes in the catalysis of several chemical reactions.…”
Section: Mineral Elementscontrasting
confidence: 66%
“…Differences in color, odor and chemical compounds are observed depending on the source and the season of gathering [15]. Moreover, some colonies seem to show more avid behavior on propolis collection.…”
Section: Introductionmentioning
confidence: 99%
“…Dereplication studies using HPLC-DAD-ESI-MS/MS identified the presence of pyrrolizidine alkaloids 7-(3-methoxy-2-methylbutyryl)-9-echimidinylretronecine and caffeoylquinic acid-O-arabinoside [42], but studies that report the isolation and identification of alkaloids from propolis using MS and NMR are rare. Trace elements such as Al, Ca, Fe, K, Mg, P, Zn, Cr, Ni, and Cu and possible toxic metals (As, Cd, and Pb) have also been reported [43][44][45].…”
Section: Other Constituentsmentioning
confidence: 99%